G235 Holding children for clinical procedures; an ethical consideration of the evidence. (27th April 2015) - Bray, L; Carter, B; Snodin, J
Abstract : Aim: This presentation will review current evidence on clinical holding and discuss how holding children, for clinical procedures against their wishes, can create tension between children's rights and agency and health professionals' duty to care and to act in the best interests of children in their care. Method: A narrative synthesis approach used systematic procedures to search and appraise the current empirical evidence relating to children being held for procedures within an acute children's care setting. Children in mental health, dental, primary care and anaesthetic settings were excluded from the review. Findings: Empirical evidence demonstrates that children are frequently held for procedures to be completed within acute care settings. The delineation between holding and restraint is poorly defined. Children's protests and distress are reported as taking lower precedence in a decision to hold a child for a procedure than either clinical need or the interests of the adults present. Parents and health professionals expressed feelings of distress, uncertainty, guilt and upset associated with clinical holding. Despite this, alternatives to holding are not always explored and health professionals maintain that the child's best interests are served by a procedure being completed quickly at the expense of short-term distress; the end justifiying the means. This approach neither takes into consideration the possible long-term psychological consequences of holding or restraining children for non-urgent procedures nor how their rights and agency are protected by the adults charged with advocating for them. Evidence suggests that current practice is weighted towards an adult centred approach and that consideration needs to be given to how practice can be tipped towards a child centred approach. Conclusion: Although children are reported as being frequently held for clinical procedures, there is very little quality empirical data or critical ethical debate to inform practice. The lack of robust evidence and clear definitions of what constitutes holding perpetuate this being an almost invisible and taken for granted part of children's care within acute settings.